Kodak's ergonomic design for people at work. - The Eastman Kodak Company (Hoboken : Wiley, 2004)
Originally published as two volumes in 1983 and 1986, this work brought together material from the published literature, internal research, and other work of the Human Factors Section/Ergonomic Group at Eastman Kodak Company. Here, the contents of that work have been condensed and combined with new material from ergonomics practitioners from outside the company. Focusing more on practice than theory, the work describes solutions to problems found in the industrial work setting, looking at issues of design of the workplace, jobs, and equipment and links to human capabilities. Topics range from the design of single pieces of equipment to considerations of the total workplace environment, as well as U.S. and international standards and regulations.